Incidental paraganglioma of the urinary bladder in a 66-year-old woman. (15th March 2013) - Christodoulidou, Michelle; Lucky, Marc; Mansour, Paul; Gammal, Mohsen
Abstract : A 66-year-old female patient was referred to drology department when a bladder mass was incidentally found on a transvaginal ultrasound scan. Cystoscopy revealed a small, smooth mass just above the trigone which appeared to be covered with normal urothelium. The histology from this growth after transurethral resection revealed a paraganglioma of the bladder. We will discuss the management of this case and literature review of this finding in this study.